Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Crystal structure, NMR and theoretical investigations on 2-(o-hydroxy-anilino)-1,4-napthoquinone - Feizi, Nourollah; Pinjari, Rahul V.; Gejji, Shridhar P.; Sayyed, Fareed B.; Gonnade, Rajesh G.; Rane, Sandhya Y. (Journal of Molecular Structure, 2010)
Crystal structure, (1)H NMR and cyclic voltammetric investigations of 2-(o-hydroxy-anilino)-1,4-napthoquinone (HAN), resulting from coupling of aminophenol with 2-hydroxy-1,4-napthoquinone, have been carried out. X-ray structure reveals that the HAN ligand crystallizes in orthorhombic space group Pca2(1) with Z = 4. forming a chain via inter-molecular O2 center dot center dot center dot H1A-O1 and C15-H15 center dot center dot center dot O3 interactions. Both (1)H NMR and cyclic voltammetry experiments suggest the titled ligand is associated and exists as dinner in d(6)-DMSO while the monomer has been predicted in CDCl(3) solution. Density functional calculations can be utilized to gauge the strength of hydrogen-bonded interactions from the (1)H chemical shifts in the NMR spectra. Self-consistent reaction field (SCRF) calculations further support the inferences drawn from cyclic voltammetry experiments. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: (1)H NMR; cyclic voltammetry; Density functional; hydrogen bonding; Napthoquinone

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.